Efektivitas Sistem Pelayanan Pembuatan Surat Izin Mengemudi (SIM) Secara Online di Satuan Penyelenggara Administrasi (Satpas) Colombo Surabaya - Fatimah, Siti (JPAP: Jurnal Penelitian Administrasi Publik, 2017)
Effectiveness of Service System Making Driver's License (SIM) Online in Administrative Administrator Unit (Satpas) Colombo Surabaya Online SIM is applied for the creation of new SIM and SIM renewal. The purpose of this research is to know and describe the effectiveness of service system of SIM making online to know and describe the constraints faced in service system of SIM making online and to know and describe effort done to improve system effectiveness of service of SIM making online. Analytical technique used is descriptive qualitative. The results showed that the effectiveness of the service of making Driver's License (SIM) online is known from several factors, namely: a) Time factor; shows that the time required in service is 15 to 20 minutes; b) Accuracy factors; indicates that the staff or the party providing online services has a high accuracy and accuracy so that in practice rarely found an error in the process of service being run; and c) Service-style factors; it is known that the style of service providers in this case is the staff or parties as performing the duties and responsibilities of work in accordance with applicable SOP and existing. The results also show that online SIM services are considered to be effective but not maximal considering there are still some obstacles in the implementation. These constraints consist of: a) there are still people who do not know clearly about the mechanism of the SIM online; b) the number of staff is considered to be lacking; c) there is a connection or network trouble; d) The Administrative Administrator Unit Colombo Surabaya still uses the conventional system in the implementation of its operational management; and e) still under renovation. In relation to the apparent constraints, efforts are made to improve the effectiveness of SIM-making services online by conducting socialization through television and radio and socializing the ball pickup system; making additional staff as needed, the Parties may cooperate with the service provider; and updating IT-based infrastructure and training in the use of information technology-based infrastructure or the Internet.Â Keywords: Effectiveness, Service, Driver License (SIM) online